2012
DOI: 10.1111/liv.12021
|View full text |Cite
|
Sign up to set email alerts
|

Pathological bacterial translocation in cirrhosis: pathophysiology, diagnosis and clinical implications

Abstract: Bacterial translocation (BT) is defined by the passage of viable indigenous bacteria from the intestinal lumen to mesenteric lymph nodes (MLNs) and other territories, and its diagnostic criteria rely on the isolation of viable bacteria in MLNs. Small intestinal overgrowth, increased intestinal permeability and immunological alterations are the main factors involved in its pathogenesis. BT is obviously difficult to identify in patients with cirrhosis, and alternative methods have been proposed instead. Bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
211
1
20

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(238 citation statements)
references
References 82 publications
(91 reference statements)
6
211
1
20
Order By: Relevance
“…A number of studies have shown that SIBO is seen more in patients with cirrhosis [18][19][20]. Miele et al found that SIBO had a high prevalence in NAFLD patients compared with normal people [21].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have shown that SIBO is seen more in patients with cirrhosis [18][19][20]. Miele et al found that SIBO had a high prevalence in NAFLD patients compared with normal people [21].…”
Section: Discussionmentioning
confidence: 99%
“…9 The increased gut permeability and the cirrhosis associated immune dysfunction (CAID) make this population prone to develop BSI by endogenous route, particularly during acute-on-chronic liver failure (ACLF). 10,11 Frequent need for hospitalization, invasive procedures and, use of indwelling devices such as central venous line or transjugular intrahepatic portosystemic shunt (TIPS), give to the exogenous route an additional pathogenetic rule, further increasing the overall risk, mainly in the setting of Health Care Associated or Hospital Acquired infections. 12,13 BSIs in LC are also associated with high mortality, prolonged hospitalization and faster escalation of the liver disease.…”
Section: Introductionmentioning
confidence: 99%
“…However, increased intestinal permeability cannot fully account for the pathophysiology of BT; moreover, it is not clear whether these structural changes are the cause or the result of BT [5] . The intestinal immune system is comprised of Peyer's patches, the mesenteric lymph nodes (MLNs) and a large number of cells distributed throughout the lamina propria and epithelium of the intestine [14,15] .…”
Section: Pathogenesis Of Btmentioning
confidence: 99%
“…The origin of such microorganisms is the enteric flora and translocation occurs via a defective mucosal barrier [4] . BT is considered the key step in the pathogenesis of SBP and bacteremia in cirrhotic patients, as well as a critical factor that triggers host immune responses and secretion of inflammatory mediators, which, ultimately, mediate the hemodynamic changes that are present in portal hypertension and cirrhosis [5] . The main three mechanisms involved in BT include bacterial overgrowth, physical disruption of the gut mucosal barrier and an impaired host defence ( Figure 1) [6] .…”
Section: Introductionmentioning
confidence: 99%